Предмет:
Другие предметыАвтор:
анонимПри решении используем формулу суммы кубов двух чисел :
x^3 + y^3 = (x + y) * (x^2 - x * y + y^2 ).
Получаем:
(b^3 + 3 * b^2 + 3 * b + 1 ) / ( b* ( 1 / b + 1 ) ) =
= (b^3 + 3 * b^2 + 3 * b + 1 ) / (b + 1) =
= ( (b^3 + 1^3) + ( 3 * b^2 + 3 * b ) ) / (b + 1) =
= ( (b + 1) * (b^2 - b * 1 + 1^2) + 3 * b * (b + 1) ) / (b + 1) =
= ( (b+1) * (b^2 - b + 1) + 3 * b * (b + 1) ) /(b + 1) =
= (b + 1) * (b^2 - b + 1 + 3 * b) / (b + 1) = b^2 - b + 1 + 3 * b =
= b^2 + 2 * b + 1 = (b + 1)^2.
Ответ : (b + 1)^2.
Автор:
katoДобавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть